PENGARUH PUPUK IKAN RUCAH DAN KANDANG PADA TANAH GARAMAN LAHAN BASAH TERHADAP BEBERAPA SIFAT TANAH SERTA HASIL TANAMAN SISTEM POT - Fachruzi, Ismed; Kurnain, Akhmad; Hadi, Abdul; Sofyan, Antar (Universitas Lambung Mangkurat, 2024)
The nature of the soil studied in the wetland area (coastal) is massive (solid) and saline, less fertile for horticultural crops such as shallots and mustard greens. Experiments using the original soil mixed with quartz sand (35% w/w), leached with ion-free water (3 liters/kg/pot), the irrigation method is soaked-drown it (1/3 of the height of the bottom of the pot) and treated with 5% organic fertilizer (w/w) in the form of fish manure (bycatch) mixed with water hyacinth-Eichornia crassipes (RE) or rice husk (RM) and manure from broiler chicken manure. Treatment per pot: K (control) = original soil (1 kg); RE = (35 g trash + 15 g water hyacinth); RM = (35 g trash + 15 g rice husk); Chicken Manure A1=50 g/pot and, A2 =100 g/pot. The results are as follows: (1) Soil properties: The highest soil water absorption content is in A1 and A2; The lowest bulk density is in A2, RE, RM; The highest pH is in RM; and the highest EC (or DHL) and does not differ in A2, RE, or R; The highest exchangeable K, Na, Ca are in A2 and exchangeable Mg are not affected; The highest organic C is in A2, the highest total N is in A2 or RM, and the lowest C/N is in RM; (2) Mustard plant properties for the age of 4-6 weeks after planting (MST): the highest plant height, the largest number of leaves, and the largest number of leaf areas are in A1 or A2, and (3) Shallot plant properties for plant height and number of shallot leaves at the age of 4, 5, and 6 MST: the highest in K, A1, or A2. Overall, the A1 or A2 treatment, namely the application of chicken manure 50-100 g/pot/kg of soil is the highet (best) result.